Sustained declines in age group-specific rotavirus infection and acute gastroenteritis in vaccinated and unvaccinated individuals during the five years since Rotavirus vaccine introduction in England - Gower, CM; Stowe, J; Andrews, NJ; Ramsay, ME; Ladhani, SN (Oxford University Press, 2021)
Background: The introduction of an oral live-attenuated monovalent rotavirus vaccine (Rotarix ®) into the UK infant immunisation programme in July 2013 was associated with large reductions in laboratory-confirmed rotavirus infections and hospitalisations due to acute gastroenteritis (AGE) within 12 months. Here we report the five-year impact of the programme in England.